Efficacy of auricular plaster therapy for sleep disorders in preschool children with autism spectrum disorders: Study protocol for a randomized controlled trial - Duan, Duoxi; He, Lin; Chen, Hong; Lei, Ying; Wu, Wei; Li, Tao (Frontiers in Neurology, 2022)
Background Children with autism spectrum disorders (ASDs) suffer from sleep disorders to a considerable degree; however, there is no safe and effective treatment available in clinical practice. The objective of the trial is to assess the clinical effectiveness of auricular plaster therapy (APT) in treating sleep disorders in children with ASD. Method This is a single-center, patient-assessor blind, randomized controlled trial. A total of 44 preschool children with sleep disorders with ASD will be included in this study. Eligible participants will be randomly assigned to either the auricular plaster group or the sham auricular plaster group in a 1:1 ratio. Participants in the different groups will receive APT or sham APT, respectively, for a total of 30 sessions over 30 days. The primary outcome includes the Children's Sleep Habits Questionnaire (CSHQ), while secondary outcomes include the Autism Behavior Checklist (ABC) and polysomnography (PSG) for total sleep time, sleep latency, awakening duration, and sleep structures. The CSHQ and ABC will be assessed at baseline, 10, 20, 30, 60, 90, and 120 days after randomization, whereas PSG will be assessed at baseline and 30 days after randomization. The follow-up period will be scheduled to be 60, 90, and 120 days after randomization. Discussion The results of this study may provide evidence of the efficacy of APT, as well as offer new alternatives for the treatment of sleep disorders in children with ASD. Trial registration CHiCTR.org.cn (ChiCTR2100048257). Registered on July 5, 2021.